Endothelin-1 receptor drives invadopodia: Exploiting how β-arrestin-1 guides the way. (3rd September 2018) - Bagnato, Anna; Rosanò, Laura
ABSTRACT: Metastatization is a complex multistep process requiring fine-tuned regulated cytoskeleton re-modeling, mediated by the cross-talk of actin with interacting partners, such as the Rho GTPases. Our expanding knowledge of invadopodia, small invasive membrane protrusions composed of a core of F-actin, actin regulators and actin-binding proteins, and hotspots for secretion of extracellular matrix (ECM) proteinases, contributes to clarify critical steps of the metastatic program. Growth factor receptors and their intermediate signaling molecules, along with matrix adhesion and rigidity, pH and hypoxia, act as drivers of cytoskeleton changes and invadopodia formation. We recently pro-posed a novel route map by which cancer cells regulates invadopodia dynamics supporting metastasis as response to the endothelin A receptor (ETA R), among the highly druggable G-protein coupled receptors in cancer. The metastatic behavior exhibited by ovarian cancer cells overe-xpressing ETA R is now explained by the interplay with β-arrestin1 (β-arr1), a scaffold protein acting as signal-integrating module of RhoC and cofilin signaling for specific invadopodia formation, accomplished by its interaction with a Rho guanine nucleotide exchange factor (GEF), PDZ-RhoGEF, in a G-protein independent manner. Here, we summarize this novel activation of the RhoC pathway from ETA R/β-arr1 signaling that may be exploited therapeutically and discuss new perspectives for future directions of investigations.